Sacrococcygeal teratoma with intraspinal extension - G. Frongia; M. Kessler; H. Bächli; J. Kunz; J.P. Schenk; M. Elsässer; B. Beedgen; A. Mehrabi; P. Günther (Elsevier, 2020)
We report a case series of two newborns with a sacrococcygeal teratoma (SCT) with intraspinal involvement. In one case, the SCT was detected prenatally and presented postnatally as a large mass of 8 × 10 × 10 cm. In the second case the prenatal ultrasound was unremarkable and the SCT presented postnatally as a rather flat one-sided gluteal mass. MRI diagnostics led to the diagnosis of extradural intraspinal involvement. In an interdisciplinary operation between pediatric surgeons and pediatric neurosurgeons a complete complications-free tumor resection was possible in both cases with a favorable postoperative course. Due to the complete resection and benign histology (Gonzales-Crussi grade 0 and 1 with exclusion of yolk sac tumor components), adjuvant measures such as chemotherapy were not necessary. At 4 months no morbidity or mortality occurred, micturition and defecation were unremarkable in both cases and neurological examinations were age appropriate. Keywords: Sacrococcygeal teratoma, Intraspinal, Surgery